Can valerian improve the sleep of insomniacs after benzodiazepine withdrawal? - Poyares, Dalva R; Guilleminault, Christian; Ohayon, Maurice M; Tufik, Sergio (Progress in neuro-psychopharmacology & biological psychiatry, 2002)
Purpose: The authors studied the sleep of patients with insomnia who complained of poor sleep despite chronic use of benzodiazepines (BZDs). The sample consisted of 19 patients (mean age 43.3±10.6 years) with primary insomnia (DSM-IV), who had taken BZDs nightly, for 7.1±5.4 years. The control group was composed of 18 healthy individuals (mean age 37±8 years). Sleep electroencephalogram (EEG) of the patients was analyzed with period amplitude analysis (PAA) and associated algorithms, during chronic BZD use (Night 1), and after 15 days of a valerian placebo trial (initiated after washout of BZD, Night 2). Sleep of control subjects was monitored in parallel. Results: Valerian subjects reported significantly better subjective sleep quality than placebo ones, after BZD withdrawal, despite the presence of a few side effects. However, some of the differences found in sleep structure between Night 1 and Night 2 in both the valerian and placebo groups may be due to the sleep recovery process after BZD washout. Example of this are: the decrease in Sleep Stage 2 and in sigma count; the increase in slow-wave sleep (SWS), and delta count, which were found to be altered by BZD ingestion. There was a significant decrease in wake time after sleep onset (WASO) in valerian subjects when compared to placebo subjects; results were similar to normal controls. Nonetheless, valerian-treated patients also presented longer sleep latency and increased alpha count in SWS than control subjects. Conclusions: The decrease in WASO associated with the mild anxiolytic effect of valerian appeared to be the major contributor to subjective sleep quality improvement found after 2-week of treatment in insomniacs who had withdrawn from BDZs. Despite subjective improvement, sleep data showed that valerian did not produce faster sleep onset; the increase in alpha count compared with normal controls may point to residual hyperarousabilty, which is known to play a role in insomnia. Nonetheless, we lack data on the extent to which a sedative drug can improve alpha sleep EEG. Thus, the authors suggest that valerian had a positive effect on withdrawal from BDZ use.